Potential statin-drug interactions: prevalence and clinical significance - Zhelyazkova-Savova, Maria; Gancheva, Silvia; Sirakova, Vera (SpringerPlus, 2014)
Statins are cholesterol-lowering drugs widely used for cardiovascular prevention. Although safe when used alone, in combination with other drugs the likelihood of adverse drug reactions increases significantly. The exposure of the Bulgarian population to coprescriptions leading to potential statin-drug interactions is currently unknown.